Synthesis of oligosaccharides of the linkage region of proteoglycans using regioselective glycosylation. Issue 25 (17th June 2020) - Ledru, Hélène; Ayela, Benjamin; Fournel-Gigleux, Sylvie; Gulberti, Sandrine; Lopin-Bon, Chrystel
Abstract : A collection of various sulfoforms of di- and trisaccharides of the linkage region of proteoglycans were prepared using a regioselective glycosylation. Preliminary results of the impact of sulfation on CSGalNAcT-1 is also reported. Abstract : Proteoglycans (PGs) are complex macromolecules that are composed of glycosaminoglycan (GAG) chains covalently attached to a core protein through a tetrasaccharide linker. Biosynthesis of PGs is complex and involves a large number of glycosyltranferases. We report herein for the first time the synthesis of a collection of various sulfoforms of the disaccharide GlcA-1, 3-β-d -Gal and trisaccharides GlcNAc-1, 4-α-d -GlcA-1, 3-β-d -Gal and GalNAc-1, 4-β-d -GlcA-1, 3-β-d -Gal using a regioselective glycosylation. Preliminary results on the impact of sulfation of these disaccharides upon recombinant chondroitin sulfate N -acetylgalactosaminyltransferase-1 (CSGalNAcT-1) involved in chondroitin sulfate chain initiation is also reported.